A newer dimension to regulation of ethics committees in India. (March 2014) - Narang, Ila; Kumari Bharota, Ishita; Raisuddin, Sheikh; Kumar Jain, Gaurav; Bharal Agarwal, Nidhi
Abstract Clinical research is a pre-requisite part of the drug discovery and development process, with the main aim to ensure the safety and efficacy of any new drug. In today's date, clinical trials are the backbone for bringing newer and better drugs to market. Although a set of established guidelines are available for governing the conduct of clinical trials in India, the ethics committees of this country are still struggling with basic issues viz, inadequate or no standard operating procedures (SOPs) and non-compliance with the Schedule Y recommendations. The ethics committee being the prime body with the responsibility of regulating clinical research, protecting and safeguarding the rights, safety and well-being of research participants, the institutions, hospitals, and pharmaceutical industries that focus on enhancing their research facilities tend to ignore the various aspects of ethics committees like composition and qualification of members forming the quorum, regular updates of ethics committees to be reported to the central authority, lack of administrative support and communication, inadequate remuneration offered to members serving to ethics committee boards, archival of records and regular auditing of the ethics committee. The central regulatory body of India CDSCO governing the conduct of clinical trial, in October 2012, under the guidance of Drugs Technical Advisory Board, laid down three major amendments in schedule Y. The present article discusses one of the new amendments laid down recently in schedule Y under rule 122 DD which states the requirements and guidelines needed for registration of ethics committees in India.